(untitled) (World of finance, 2024)
Introduction. Debt collection related to the common transit operation is one of the areas of international cooperation between the countries participating in the international transit system deployed in Europe. The article examines the process of determining in Ukraine guaranteed obligations to pay a debt that may arise in relation to goods placed under the common transit procedure in force in the European Union. The main attention is paid to the issue of the same interpretation and use of the term “debt” in the context of the provisions of acts of international and national legislation in relation to the common transit procedure. The existing legal basis for objectification/determination, verification and control by customs authorities of the amount of potential debt is analyzed. In the proposals formulated in this article, directions for improvement of domestic legislation are defined, which are important for the harmonization and development of the common transit procedure in Ukraine The purpose of the article is to analyze the practice of determining the obligations secured by guarantees in the application of the common transit procedure and substantiating proposals for improving the process of determining, verifying and collecting the amounts of obligations secured by guarantees. Methods. During the study, a comparative legal method was used when working out the norms of international and domestic legislation regarding the application of the common transit procedure, methods of analysis and synthesis regarding the aspects of determining obligations secured by guarantees during common transit. Results. The process of joining Ukraine to the international transit system operating in the European Union and the use of financial guarantees to ensure the payment of debts related to the application of the common transit procedure is characterized. This made it possible to determine and propose the introduction of the same interpretation and use of the term “debt” in the context of the provisions of the acts of the current international legislation, as well as the creation of a legal basis for the objectification/determination, verification and control by customs authorities of the amount of the guarantee intended to cover the debt, in the case of applying the common transit procedure. Perspectives. It is advisable to continue scientific research on the use of the common transit procedure in Ukraine, taking into account the need for improvement, in particular, mutual assistance in the collection of claims under the joint transit procedure, which will lead to the need to finalize the national legislation in terms of introducing the necessary debt collection mechanisms, the possibility of transferring debt collection from one country to another.